Optimizing nanocarbon shell in zero-valent iron nanoparticles for improved electron utilization in Cr(VI) reduction. (March 2020) - Zhou, Na; Gong, Kedong; Hu, Qian; Cheng, Xiang; Zhou, Juying; Dong, Mengyao; Wang, Ning; Ding, Tao; Qiu, Bin; Guo, Zhanhu
Abstract: A core-shell structured zero-valent iron@carbon (ZVI@C) nanocompoiste was designed to improve the electron utilization of ZVI in the Cr(VI) reduction. The porosity of carbon layer in ZVI@C was optimized for improving the efficiency of electron utilization of ZVI in the Cr(VI) reduction process. The porous structure of carbon layer was controllably synthesized by adjusting the carbon source and the ratio of C/Fe in the precursor. The glucose was suggested as the optimal carbon source, and a high specific surface area (37.067 m 2 /g) was reached for the prepared ZVI@C when the ratio of C/Fe was controlled at 20. These ZVI@C performed well on Cr(VI) reduction, e.g. a complete reduction of Cr(VI) (2 mg/L) to Cr(III) within 10 min. The removal capacity (800 mg/g) exceeded previously recorded ZVI based adsorbents. The pH and initial Cr(VI) concentration were demonstrated as the key factors for the efficient electron utilization of ZVI. Furthermore, the efficiency of electron utilization of the ZVI increased up to 80% when the concentration of Cr(VI) was 2000 mg/L and the pH was controlled at 3, which was much higher than 8% of the naked ZVI. Graphical abstract: Core-shell structure improves electron utilization efficiency of ZVI in Cr(VI) reduction by up to 87.8%. Image 1 Highlights: Core-shell structure was designed to improve ZVI utilization in Cr(VI) reduction. Carbon shell was controlled with different molecular weight carbon precursors. The efficiency of electron utilization of ZVI was increased up to 80%.